2023
DOI: 10.1002/smll.202304483
|View full text |Cite
|
Sign up to set email alerts
|

Functional MXenes: Progress and Perspectives on Synthetic Strategies and Structure–Property Interplay for Next‐Generation Technologies

Depeng Meng,
Minghua Xu,
Shijie Li
et al.

Abstract: MXenes are a class of 2D materials that include layered transition metal carbides, nitrides, and carbonitrides. Since their inception in 2011, they have garnered significant attention due to their diverse compositions, unique structures, and extraordinary properties, such as high specific surface areas and excellent electrical conductivity. This versatility has opened up immense potential in various fields, catalyzing a surge in MXene research and leading to note worthy advancements. This review offers an in‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 248 publications
0
4
0
Order By: Relevance
“…A series of MXenes models with the M 2 CO 2 formula were first constructed, where M refers to transition metal elements from groups IV (Ti, Zr, and Hf), V (V, Nb, and Ta), and VI (Cr, Mo, and W). Preparation of the MXene from its bulk MAX phase by etching and exfoliation typically results in MXene surfaces terminated with OH, F, and O groups. , Recently, the pristine MXene without surface termination and the uniform O-terminated MXene surfaces have been successfully synthesized by substitution and elimination of surface terminal groups in inorganic molten salts . More importantly, microkinetic simulations suggested that more than 96% of the MXene surface was covered by O* groups due to facile CO 2 dissociation at the typical CO 2 -ODHP conditions (Table S6).…”
Section: Methods and Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of MXenes models with the M 2 CO 2 formula were first constructed, where M refers to transition metal elements from groups IV (Ti, Zr, and Hf), V (V, Nb, and Ta), and VI (Cr, Mo, and W). Preparation of the MXene from its bulk MAX phase by etching and exfoliation typically results in MXene surfaces terminated with OH, F, and O groups. , Recently, the pristine MXene without surface termination and the uniform O-terminated MXene surfaces have been successfully synthesized by substitution and elimination of surface terminal groups in inorganic molten salts . More importantly, microkinetic simulations suggested that more than 96% of the MXene surface was covered by O* groups due to facile CO 2 dissociation at the typical CO 2 -ODHP conditions (Table S6).…”
Section: Methods and Modelsmentioning
confidence: 99%
“…As a burgeoning class of two-dimensional (2D) materials, MXenes, including transition metal carbides, nitrides, and carbonitrides, have shown to be highly effective for thermal catalysis. The strong metal–support interaction (SMSI) and diverse physio-chemical properties make MXenes a robust platform in tailoring the morphology and electronic structures of the supported metals. Recently, MXene-supported Pt catalysts showed great potential in selective activation of the C–H bonds in alkanes. , Our group theoretically evaluated the potential application of MXene-supported metallic Pt for DDHP, and predicted that the Pt atomic layer supported on Mo 2 C and W 2 C would significantly improve propylene selectivity with comparable activity of propane conversion compared with the pure Pt(111) and Pt 3 Sn­(111) surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…As an excellent conductive material, Ti 3 C 2 T x (MXene) is a class of transition metal carbides/nitrides acquired by chemically etching the MAX phase. , MXene is considered to have better EMI shielding properties than conventional carbon-based materials owing to its superb electrical conductivity . At the same time, MXene has attracted wide attention for improving hydrogel conductivity and EMI shielding due to its excellent hydrophilicity.…”
Section: Introductionmentioning
confidence: 99%
“…MXenes, discovered in 2011, display exceptional electrical conductivity, possess numerous active sites, and demonstrate chemical stability, making them promising two-dimensional materials for photocatalytic H 2 evolution. The optimal utilization of MXene occurs when it is combined with semiconductor materials, resulting in enhanced charge transfer, suppression of carrier recombination, and consequently, improved photocatalytic performance. , Ti 3 C 2 , a renowned MXene, has been extensively studied for its ability to enhance photocatalytic H 2 evolution when combined with semiconductor photocatalysts . Ti 3 C 2 T x MXene and g-C 3 N 4 were created on polystyrene microbeads via electrostatic interaction, enhancing surface area, light absorption, and charge separation efficiency for excellent H 2 production .…”
Section: Introductionmentioning
confidence: 99%